Synthesis, In silico and Biological Studies of Thiazolyl-2h-chromen-2-one Derivatives as Potent Antitubercular Agents - Jadhav, Bhagwat S.; Yamgar, Ramesh S.; Kenny, Rajesh S.; Mali, Suraj N.; Chaudhari, Hemchandra K.; Mandewale, Mustapha C. (Current Computer - Aided Drug Design, 2020)
Background: A series of new six thiazolyl-2-amine-based Schiff base derivatives (4a-4f) were synthesized by a sequential multistep reaction starting with Salicylaldehyde. Methods: All the Schiff base derivatives were screened in-vitro for their antibacterial activity against Mycobacterium tuberculosis (H37RV strain) ATCC No-27294. The synthesized compounds were characterized by FTIR, 1H-NMR, 13C-NMR and Mass spectrometry. Results: Among the compounds tested, 4c and 4f derivatives exhibited potent antitubercular activity against M. tuberculosis at MIC 6.25 μg/mL. Conclusion: We extended our study to explore the inhibition mechanism by conducting molecular docking analysis by using Schrodinger’s molecular modeling software. All the newly synthesized compounds were found to be in-silico AMES test non-toxic and non-carcinogens. The good Qikprop’s Absorption, Distribution, Metabolism and Excretion (ADMET) would definitely help the researchers in order to make more potent Anti-TB agents.
Keywords: heterocyclic